CAPITALISATION ERRORS IN WRITTEN WORKS OF LEARNERS OF LATVIAN AS A FOREIGN LANGUAGE - Kļavinska, Antra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Capitalisation in writing is usually determined by tradition. Different written languages can have their own grammatical, conceptual or stylistic capitalisation rules. Orthographies exist which do not have the division into capital and small letters. The aim of the article is to find out what problems with capitalisation foreign students in Latvian higher education institutions have during the acquisition of writing skills in Latvian as a foreign language. The research source are the essays written by learners of the Latvian language (foreign students studying in Latvian higher education institutions): the data of the Latvian language learner text corpus being created in the Institute of Mathematics and Computer Science of the University of Latvia were used. The requirements for the acquisition of capitalisation in the context of language learner competences are analysed in the study; the most typical capitalisation errors and possible reasons for them are analysed; and the author’s practical experience teaching the Latvian language to foreign students is revealed.